2023
DOI: 10.3390/plants12122389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salicylic Acid and Macro- and Micronutrients through Foliar and Soil Applications on the Agronomic Performance, Physiological Attributes, and Water Productivity of Wheat under Normal and Limited Irrigation in Dry Climatic Conditions

Abstract: Ensuring food security with severe shortages of freshwater and drastic changes in climatic conditions in arid countries requires the urgent development of feasible and user-friendly strategies. Relatively little is known regarding the impacts of the co-application (Co-A) of salicylic acid (SA), macronutrients (Mac), and micronutrients (Mic) through foliar (F) and soil (S) application strategies on field crops under arid and semiarid climatic conditions. A two-year field experiment was designed to compare the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…However, the exact mechanisms in this process are not yet fully understood [78]. In a word, recent studies made remarkable advances in SA's roles in plant tolerance responses to both biotic and abiotic stresses [47,48,71,72,82,84,[86][87][88][118][119][120][121][122][123], and in both physiological [124][125][126] and molecular perspectives [127][128][129][130]. For example, Yao et al proposed a high air humidity-triggered significant suppression of SA accumulation and signaling associated with compromised immunity of Arabidopsis plants [130], which indicates the value of research concerning SA's roles in multiple stresses confronted by plants.…”
Section: Biosynthetic Pathway Of Sa In Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the exact mechanisms in this process are not yet fully understood [78]. In a word, recent studies made remarkable advances in SA's roles in plant tolerance responses to both biotic and abiotic stresses [47,48,71,72,82,84,[86][87][88][118][119][120][121][122][123], and in both physiological [124][125][126] and molecular perspectives [127][128][129][130]. For example, Yao et al proposed a high air humidity-triggered significant suppression of SA accumulation and signaling associated with compromised immunity of Arabidopsis plants [130], which indicates the value of research concerning SA's roles in multiple stresses confronted by plants.…”
Section: Biosynthetic Pathway Of Sa In Plantsmentioning
confidence: 99%
“…Effective mitigation of adverse impact; facilitation of better germination and early seedling growth; maintenance of relative water content, membrane stability and overall plant growth [77] salt wheat Alleviation of plant growth inhibition; increment of N, P, and K + acquisition; enhancement of endogenous SA and SPM levels by exogenous SA and/or SPM applications [82] salt St John's wort Improvement of growth [83] salt wheat Salt stress alleviation by SA and/or SPM; significant improvement of growth and production [84] drought wheat Substantial reduction of drought influence, and enhancement of grain yield and water use efficiency by co-application of K + and SA [85] dry climatic conditions wheat Attenuation of deficit irrigation, and improvement of growth and production by co-application of essential plant nutrients and SA [86] drought wheat Regulation of stress response [87] cadmium tomato Significant reduction of cell wall Cd accumulation; changes in Cd distribution [90] waterlogging stress soybean Reduction of some physiological indexes by SA and KN; enhancement of antioxidant defense by SA and KN; effective improvement of ROS metabolism and waterlogging stress tolerance [94] salt cashew Attenuation of salt stress; increment of photosynthetic pigment synthesis [97] drought oregano Improvement of PSII efficiency under moderate drought stress [98] water deficit and nutrient deprivation Sempervivum tectorum L.…”
Section: Camellia Oleiferamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, spraying wheat plants with SA and zinc reduced the negative effects of water deficiency, leading to increased chlorophyll content, relative water content, plant height, spike length, number of grains per spike, 1000-grain weight, grain yield, and water use efficiency [ 35 ]. Likewise, Alotaibi et al [ 36 ] concluded that combining micronutrients with SA is more effective in enhancing the growth, yield parameters, and irrigation water use efficiency (IWUE) of wheat plants under water deficit compared to using these compounds individually. Safar-Noori et al [ 37 ] found that combining SA with a sufficient amount of K enhanced wheat growth and production under drought stress more effectively than applying them separately.…”
Section: Introductionmentioning
confidence: 99%